Marketing Communication Strategy of Kampoeng Heritage Kajoetangan Malang using SOSTAC Model - Maghfira, Viola Fardhi (Advances in Social Sciences Research Journal, 2021)
This study explores how marketing communication strategies in thematic villages are described with the SOSTAC model. This research aims to analyze the marketing communication strategy that has been carried out by Kampoeng Heritage Kajoetangan Malang using the SOSTAC Model. To achieve this objective, this study uses descriptive research, which means that this research describes systematic, factual, accurate from the data obtained and then analyzed to obtain the results needen in the study. The results showed that in the KJT village the marketing communication strategy that had been carried out had gone well using marketing communication tools such as publicity, direct marketing, personal selling, word of mouth to attract visitors. The focus of KJT for marketing communication strategies is image, tourist attraction, advances in information technology. The marketing communication strategy that shows the interest of Kampoeng Heritage Kajoetangan is dutch era buildings that are still well cared for and preserved to become a characteristic of Malang city which is identical to a heritage city.